KRIMINALISASI KEMISKINAN: STUDI KRIMINOLOGI TERHADAP PRAKTIK PENGGUSURAN PAKSA DI PERKOTAAN - Arrasyid Wiriadihardja, Mochamad Keizar (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Forced evictions of urban poor communities are often justified in the name of development, spatial planning, or public interest. However, these actions reflect a form of criminalization of poverty, in which the existence of the poor is constructed as a social problem to be eliminated rather than humanized. This paper aims to analyze forced eviction practices through a critical criminological perspective, focusing on the concepts of state crime and structural violence. The research method employed is qualitative-descriptive using literature study and theoretical analysis. The findings indicate that forced evictions are manifestations of systemic marginalization driven by political-economic power. Therefore, they must be viewed as violations of human rights rather than mere administrative actions.